Faulty Node Detection in Multirate anypath Routing Protocol in Multi-Hop Wireless Networks (International Journal of Engineering and Computer Science, 2013)
In wireless sensor networks consist of several sensor nodes are enveloping and forward their information to nearest neighborhood nodes. The sensors nodes are to join forces and achieve coordinate their operations, it is necessary to preserve the transmission at all times. In this case distance end to end of the intermediate node communication path can be constrained to detection of nodes, efficient communication, and latency. Therefore a faculty node of can be detect in the several network topology, effective Modern recovery methodologies schemes considered every nodes need to communicate with only those nodes that are within its communication range and is to in a parallel reposition a divide of the performer nodes to restore connectivity. Already solved this presenting multi rate any path routing and provide the proof of its optimality existing route discovery activities does not focused on failure node communication in multi rate any path routing protocol. We proposed an algorithm of Distributed Cut Detection algorithm is a distributed iterative for Detection of faulty node in multi rate any path routing for multi hop wireless networks with Reliable Communication. The connectivity is to a specially elected node has been lost, and one or more nodes to detect the occurrence of the detecting the partition independent of the size and structure of the network